Runoff Modeling to Inform Policy Regarding Development of Green Infrastructure for Flood Risk Management and Groundwater Recharge Augmentation along an Urban Subcatchment, Ciudad Juarez, Mexico. (December 2016) - Granados‐Olivas, Alfredo; Alatorre‐Cejudo, Luis Carlos; Adams, David; Serra, Yolande L.; Esquivel‐Ceballos, Víctor Hugo; Vázquez‐Gálvez, Felipe Adrián; Giner, Maria Elena; Eastoe, Chris
Abstract: Changes in land use patterns at expanding border cities along the U.S.‐Mexico transboundary area have severe impacts on runoff coefficients and flood risk management. Severe rain is the most representative type of precipitation in the Paso del Norte (PdN) region (New Mexico and Texas in the United States and Chihuahua in Mexico), characterized by high intensity, low duration, and high volumes of rain falling in localized, small areas. Rains generate flooding and damage to urban infrastructure, putting at risk people and properties along the arroyos, which lack hydraulic design to control overflowing. While using a Geographic Information System (GIS), we applied the Hydrologic Modeling System (HEC‐HMS) to model streamflow at the study site while building the hydrologic domain using ArcGIS with the Flow Area extension. Flood risk analysis was generated to evaluate potential sites for establishment of Green Infrastructure (GI) as a means of reducing risk and induce recharge to local aquifers. A hydrologic model was created using HEC‐HMS under GIS tools and later using Flood Area® hydrologic software to evaluate flood risk analysis. For small‐scale watersheds (< 10 km 2 ) runoff can be greatly reduced by using and developing an urban hydrology approach. Furthermore, using GI and applying an urban hydrology approach can generate synergistic benefits by reducing flood risk, enhancing recharge to aquifer formations, weakening urban heat islands, improving habitat for regional species, and generating a common site for social interaction between neighbors. Binational agencies have adapted a new policy to address and promote the generation of such sites while academia, local government, and Non‐Governmental Organizations (NGOs) have taken up the challenge of promoting joint collaboration leading to local solutions to the ancient problem of flood risk.